KUALITAS PAPAN KOMPOSIT SERAT KULIT BATANG SAGU DAN PLASTIK POLIPROPILENA (PP) BERLAPIS FINIR DAN BAMBU - Umam, Tajul; Setyawati, Dina; Diba, Farah (JURNAL HUTAN LESTARI, 2017)
This research aim to determine of immersion types and the addition of layer materials on the physical and mechanical composite board and to determine the best treatment. Composite board made with size 30 cm x 30 cm x 1 cm with 0,7 gr/cm3 density target. Physical and mechanical testing based on JIS A 5908 – 2003 standard. This research using factorial experiments pattern on completely random design with 2 treatment factor, namely immersion factor which consist of two sub factor (hot water immersion and cold water immersion) and composite board layer factor which consist of 3 sub factor (without layer, finir layer and bamboo layer). Materials mixing doing manually with Polypropylena distribution is divided into 3 parts, each of face and back is 15 %, and core is 70 % from plastic weight. Hot press conducted on temperature 1800C with ± 25kgf/cm2 during 10 minutes. Research result showed that every composite board is according to JIS A 5908 – 2003 standard, except water content value is lower than standard. Finir layer composite board with hot water immersion during 2 hours is the most optimal. Keyword : Composite Board, Immersion, Layer, Physical and Mechanical, Polypropylena Plastic